The Role of Public Policies in Increasing Foreign Direct Investments - Amin Taghiyev (PT. EQUATOR SINAR AKADEMIA, 2023)
Public policies play a crucial role in facilitating and promoting foreign direct investments (FDI) within a nation. This study examines the influence of government policies on foreign direct investment (FDI) inflows and delineates essential approaches for fostering the attraction of international investors. This study identifies five primary elements that exert influence on foreign direct investment (FDI) through the implementation of public policies. These aspects include investment incentives, the regulatory environment, infrastructure development, political stability, and trade agreements. Through a comprehensive analysis of these elements, governments have the ability to formulate policies that effectively stimulate Foreign Direct Investment (FDI) and foster substantial economic growth. The present analysis underscores the significance of a conducive investment environment, encompassing tax incentives, streamlined regulatory frameworks, and efficient infrastructure. The presence of political stability and a strong adherence to the rule of law creates a favorable and secure climate for potential investors. Finally, engaging in active involvement in international trade agreements has the potential to enhance market access and strengthen foreign direct investment (FDI). In summary, it can be argued that the implementation of effective public policies has the potential to greatly enhance foreign direct investment (FDI), hence stimulating economic growth and promoting international interconnectedness.